Assessment of the Burnout Level in Health Care Worker During COVD 19 - Mustafa Kareem Jawad1; Dhiaa Abd Al-Rasoul Abd Al-Reda; Waleed Ali Armeah; Asmaa Jabbar Abdulhussein (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Health care workers are considered the first and real resisting line in the face of the COVID19 pandemic, and therefore they have an greater workload, tension and the stress. Understanding the risks of burnout is very important to support healthcare workers and also to maintain high-quality health care through an epidemic. Methods: A cross-sectional study design could be used to assessment the level of burnout during COVID 19. Included 1000 samples as a healthcare worker involved in the study by used of convenience sampling technic , The study has been carried out in Iraqi, conducted throughout the period of April 15th, to July 19th, 2020. A self-questionnaire and Maslach Burnout Inventory Human Service Survey were used to data collect. Results: Overall, burnout were high level among 59.9 % of participation in the study. Workload high and intention to leave were related with burnout at statistically significant (P<0.05), and high significant relationship between demographic characteristics (age, gender, level of education, job title, work place ) and level of burnout (P<0.05).Conclusions: The study found that the increase in the level of fatigue that was identified among health workers was associated with high workload and psychological stress fronting them during COVID 19, as well as the lack of personal equipment necessary to protect themselves from this epidemic.